find all the roots and check your answers. x^2 + 5x - 14 = 0

Question

Asked 3/14/2013 11:49:01 PM

Updated 223 days ago|7/25/2023 2:14:49 PM

4 Answers/Comments

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

OxTornado007|Points 6729|

OxTornado007|Points 6729|

Question

Asked 3/14/2013 11:49:01 PM

Updated 223 days ago|7/25/2023 2:14:49 PM

4 Answers/Comments

Rating

3

The roots of the quadratic equation 3x^2 + 5x = 0 are x = 0 and x = -5/3.

Added 223 days ago|7/25/2023 2:13:12 PM

This answer has been flagged as incorrect.

Deleted by •|Don [7/25/2023 2:13:19 PM]

3

The roots of the equation 3x^2 + 5x = 0 are: x = 0 and x = -5/3.

Verification:

For x = 0: 3(0)^2 + 5(0) = 0 (True)

For x = -5/3: 3(-5/3)^2 + 5(-5/3) = 0 (True)

Verification:

For x = 0: 3(0)^2 + 5(0) = 0 (True)

For x = -5/3: 3(-5/3)^2 + 5(-5/3) = 0 (True)

Added 223 days ago|7/25/2023 2:13:48 PM

This answer has been confirmed as correct and helpful.

3

The roots of the equation 49x^2 - 25 = 0 are: x = 5/7 and x = -5/7.

Verification:

For x = 5/7: 49(5/7)^2 - 25 = 0 (True)

For x = -5/7: 49(-5/7)^2 - 25 = 0 (True)

Verification:

For x = 5/7: 49(5/7)^2 - 25 = 0 (True)

For x = -5/7: 49(-5/7)^2 - 25 = 0 (True)

Added 223 days ago|7/25/2023 2:14:21 PM

This answer has been confirmed as correct and helpful.

3

The roots of the equation 4x^2 - 13x + 3 = 0 are: x = 1/4 and x = 3.

Verification:

For x = 1/4:

4(1/4)^2 - 13(1/4) + 3 = 0

4/16 - 13/4 + 3 = 0

1/4 - 13/4 + 3 = 0

(1 - 13 + 12)/4 = 0

0 = 0 (True)

For x = 3:

4(3)^2 - 13(3) + 3 = 0

4(9) - 39 + 3 = 0

36 - 39 + 3 = 0

0 = 0 (True)

Verification:

For x = 1/4:

4(1/4)^2 - 13(1/4) + 3 = 0

4/16 - 13/4 + 3 = 0

1/4 - 13/4 + 3 = 0

(1 - 13 + 12)/4 = 0

0 = 0 (True)

For x = 3:

4(3)^2 - 13(3) + 3 = 0

4(9) - 39 + 3 = 0

36 - 39 + 3 = 0

0 = 0 (True)

Added 223 days ago|7/25/2023 2:14:49 PM

This answer has been confirmed as correct and helpful.

Add or substract the follow polynomials as indicated: (5.9x^3 +3.4x^2 - 7) - (2.9x^3 -9.6x^3) - (9.6x^2 + 3)
**Weegy:** (5.9x^3 +3.4x^2 - 7) - (2.9x^3 -9.6x^3 - 9.6x^2 + 3) = 12.6x^3+13.x^2-10 **User:** multiply. (6x +7)(3x+2) **Weegy:** (6x+7)(3x+2) = 18x^2+33x+14 **User:** Multiply. (4x + 1)(2x^2 + x + 1) **Weegy:** 5/2x+1/4x=7/4+x SOLUTION:
5/2x+1/4x-x=7/4 >>
(5/2+1/4-1)x=7/4 >>
(7/4)x=7/4 >>
x=(7/4)/(7/4) >>
x=1 (More)

Question

Updated 4/30/2015 2:33:25 AM

1 Answer/Comment

(4x + 1)(2x^2 + x + 1)

=8x^3+2x^2+4x^2+x+4x+1

=8x^3+6x^2+5x+1

=8x^3+2x^2+4x^2+x+4x+1

=8x^3+6x^2+5x+1

Added 4/30/2015 2:33:25 AM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [4/30/2015 2:53:40 AM]

Use the difference of two squares forumula to factor. 4x^2 - 25
User: Use the difference of two squares forumula to factor. 81x^2 - 1
**Weegy:** Solution:
81x^2-1 = (9x)^2-1^2 = (9x+1)(9x-1) ; therefore the answer is (9x+1)(9x-1) .
(More)

Question

Expert Answered

Updated 4/30/2015 2:52:10 AM

1 Answer/Comment

4x^2 - 25

= (2x)^2 - 5^2

= (2x - 5)(2x + 5)

= (2x)^2 - 5^2

= (2x - 5)(2x + 5)

Added 4/30/2015 2:37:51 AM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [4/30/2015 2:52:19 AM]

38,928,452

questions answered

There are no comments.